PENGARUH POLITIK DALAM PEMBENTUKAN HUKUM DI INDONESIA - Salam, Abdus (IAIN Samarinda, 2015)
This article examines how the politics influence legal development in Indonesia. Politics and law are two things that influence each other. In the process of establishing the rule of law by political institutions, the role of political forces who sit in the political institutions are very decisive.Â When the position of law is more determinant than politics, then political activities are regulated by and must comply to legal rules. On the other hand, when politics is more determinant than law, then law is a product of political wills that interacts each other and even competes each other. However, an ideal system is a system when both law and politics are in balance in terms of determination. In such condition, an order may be achieved.